2017
DOI: 10.15446/agron.colomb.v35n1.64135
|View full text |Cite
|
Sign up to set email alerts
|

Banana leaf as packaging of lulo for different storage temperatures and the effects on postharvest characteristics

Abstract: In Colombia, the small and médium farmers are responsible for the production of nearly 45.000 t yr-1 of lulo (Solanum quitoense). However adequate and easy techniques for postharvest handling are not often available to be implemented by this sector of the producers. This research aimed to study banana (Musa paradisiaca) leaf as primary packaging to minimize the loss of quality of lulo stored at different temperatures. Chemical and physiological quality parameters were considered in the analysis of the maturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Banana leaves were employed as crucial packaging to prevent lulo fruit from losing quality and firmness during storage period. This study suggested that the banana leaves can be used to maintain the consistency of the fruit over an extended period of storage by reducing weight losses and color changes (Forero‐Cabrera et al, 2017).…”
Section: Applications Of Banana and Its By‐products In Food Industrymentioning
confidence: 99%
“…Banana leaves were employed as crucial packaging to prevent lulo fruit from losing quality and firmness during storage period. This study suggested that the banana leaves can be used to maintain the consistency of the fruit over an extended period of storage by reducing weight losses and color changes (Forero‐Cabrera et al, 2017).…”
Section: Applications Of Banana and Its By‐products In Food Industrymentioning
confidence: 99%
“…Furthermore, the leaves are often used as wrappers for cooking dishes, including those that may be steamed, roasted, deep-fried, or grilled, in which the filling ingredients are shielded from flame-burning while still adding the flavor of the leaves (Kora, 2019). Forero-Cabrera et al (2017) used banana leaves as critical packaging to reduce the loss of quality, particularly firmness, of lulo fruit stored at different temperatures. The weight losses and color changes caused by the ripening process were reduced, indicating that this banana by-product can be used to preserve the consistency of this fruit over a long storage period.…”
Section: Banana Leavesmentioning
confidence: 99%
“…Es necesario garantizar un buen manejo poscosecha que permita la conservación de la calidad de los frutos obtenida en condiciones de campo, con el fin de disminuir las pérdidas durante el almacenamiento y comercialización, ya que estas son muy altas y llegan a alcanzar valores que oscilan entre 10 % y 30 % de la producción (Forero-Cabrera et al, 2017). Los frutos de lulo se clasifican como climatéricos, por lo tanto, una vez son separados de la planta continúan los procesos inherentes a la maduración en condiciones favorables durante la etapa posterior a la cosecha.…”
Section: Morillo Et Al (2019) Evaluaron Lasunclassified